Hedonic analysis of the price of mangalarga marchador horses sold at auctions - Marquez , Mahara Moreira; Santos, Brenda Alves Alves dos; Mamede, Larissa Ferreira; Schultz, Erica Beatriz; Silva, Natascha Almeida arques da; Raineri, Camila (Acta Scientiarum. Animal Sciences, 2023)
The objective was to identify sets of relevant atributes for pricing Mangalarga Marchador horses at auctions and to estimate a hedonic pricing function. We analyzed 452 horses at 20 auctions. The studied variables were characteristics intrinsic to the animals and attributes that influence sale price, which were identified through generalized linear and logistic model analysis. For each additional prize and additional bid, the prices decreased by R 2110.00 and R 549.00 respectively. The individual’s maternal grandsire positively or negatively affected prices, from R - 86.70 to R + 35.50. Non-pregnant females were penalized in price by R 110.00 compared to non-castrated males. A bay coat added R 215.00 to prices when compared to chestnut animals. Online auctions added R 20.10 to prices and virtual auctions penalized prices by R 617.00. The gray coat devalues a sale by 48% and Seller 3 decreasing by 18%. We conclude that auction type, number of prizes, share sold, animal category, coat, seller, number of bids, and maternal grandsire influenced the prices of Mangalarga Marchador horses, and that coat and seller that influenced the probability of the animal being sold.